2021
DOI: 10.1002/clc.23604
|View full text |Cite
|
Sign up to set email alerts
|

Residual alterations of cardiac and endothelial function in patients who recovered from Takotsubo cardiomyopathy

Abstract: Introduction Takotsubo cardiomyopathy (TCM) is characterized by transient left ventricle dysfunction. Hypothesis A residual cardiac and endothelial dysfunction is present in patients who recovered from TCM. Methods In this single‐center prospective study, patients with prior TCM were included and followed for 6.4 ± 1.6 years. All underwent comprehensive cardiac function assessment, including tissue Doppler imaging (TDI) and 2‐dimensional strain (2DS) echocardiography at their first visit. The number of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…CMR-FT is useful for evaluating LV deformation of TTS, and the transient contraction abnormalities in TTS can be quantitatively assessed with CMR-FT [ 8 ]. Some studies reported residual alterations of cardiac deformation in TTS patients using two-dimensional strain echocardiography [ 9 ]. A few data have been published on residual changes in cardiac function of patients with prior recovered TTS using CMR-FT showing deformation abnormalities that may persist despite normalization of global LV function at follow-up of 3 months [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMR-FT is useful for evaluating LV deformation of TTS, and the transient contraction abnormalities in TTS can be quantitatively assessed with CMR-FT [ 8 ]. Some studies reported residual alterations of cardiac deformation in TTS patients using two-dimensional strain echocardiography [ 9 ]. A few data have been published on residual changes in cardiac function of patients with prior recovered TTS using CMR-FT showing deformation abnormalities that may persist despite normalization of global LV function at follow-up of 3 months [ 8 ].…”
Section: Introductionmentioning
confidence: 99%